Transformation of the landscape - Mumbai Archive Project Team (Jio Institute, 2024)
This road in Kandivli village used to be a maidan (playground) until 1985. Ramnath Keny fondly recalls spending hours on this ground playing kabaddi with his friends. However, the landscape has transformed over the years, and the open space is now a traffic intersection surrounded by high-rise buildings.